Dual material gate nanowire field effect diode (DMG-NWFED): Operating principle and properties. (January 2018) - Vadizadeh, Mahdi
Abstract: In this paper the impacts of warp-around gates on the electrical characteristics of a field effect diode (FED) have been presented in terms of I ON /I OFF ratio and gate delay by a numerical simulator. Simulation results show that quantum confinement effects result in nanowire regular FED (NWRFED) does not meet the drive current requirements predicted by the international technology roadmap for semiconductors (ITRS). By employing the gates with a different workfunction, we propose a "dual material gate nanowire FED (DMG- NWFED)" structure which supports the drive current requirements predicted by ITRS. Numerical simulations show that the subthreshold slope ( SS ) of the proposed structure is 53 mV/dec. In addition, the I ON /I OFF ratio in DMG-NWFED is approximately thirteen orders of magnitude bigger than I ON /I OFF ratio in NWRFED. The proposed structure provides a negative differential resistance (NDR) characteristic for 7.5 nm channel length and 3 nm nanowire diameter. This perhaps renders DMG-NWFED a prominent candidate for multilevel digital circuit applications due to its NDR characteristic. Highlights: The gate all around nanowire regular FED (NWRFED) device has been considered to reduce the leakage current. However, simulation results show that strong quantum confinement effects result in the reduced drive current for NWRFED. We propose a "dual material gate NWFED (DMG-NWFED)" structure by modification of NWRFED. The ION /IOFF ratio in DMG-NWFED is approximately thirteen orders of magnitude bigger than ION /IOFF ratio in NWRFED. The proposed structure provides a NDR characteristic for 7.5 nm channel length and 3 nm nanowire diameter.